Systematic assessment of environmental risk factors for bipolar disorder: an umbrella review of systematic reviews and meta‐analyses. (3rd May 2017) - Bortolato, Beatrice; Köhler, Cristiano A.; Evangelou, Evangelos; León‐Caballero, Jordi; Solmi, Marco; Stubbs, Brendon; Belbasis, Lazaros; Pacchiarotti, Isabella; Kessing, Lars V.; Berk, Michael; Vieta, Eduard; Carvalho, André F.
Abstract : Objectives: The pathophysiology of bipolar disorder is likely to involve both genetic and environmental risk factors. In our study, we aimed to perform a systematic search of environmental risk factors for BD. In addition, we assessed possible hints of bias in this literature, and identified risk factors supported by high epidemiological credibility. Methods: We searched the Pubmed/MEDLINE, EMBASE and PsycInfo databases up to 7 October 2016 to identify systematic reviews and meta‐analyses of observational studies that assessed associations between putative environmental risk factors and BD. For each meta‐analysis, we estimated its summary effect size by means of both random‐ and fixed‐effects models, 95% confidence intervals (CIs), the 95% prediction interval, and heterogeneity. Evidence of small‐study effects and excess of significance bias was also assessed. Results: Sixteen publications met the inclusion criteria (seven meta‐analyses and nine qualitative systematic reviews). Fifty‐one unique environmental risk factors for BD were evaluated. Six meta‐analyses investigated associations with a risk factor for BD. Only irritable bowel syndrome (IBS) emerged as a risk factor for BD supported by convincing evidence ( k =6; odds ratio [OR]=2.48; 95% CI=2.35−2.61; P <.001), and childhood adversity was supported by highly suggestive evidence. Asthma and obesity were risk factors for BD supported by suggestive evidence, and seropositivity to Toxoplasma gondii and a history of head injury were supported by weak evidence. Conclusions: Notwithstanding that several environmental risk factors for BD were identified, few meta‐analyses of observational studies were available. Therefore, further well‐designed and adequately powered studies are necessary to map the environmental risk factors for BD.